2022
DOI: 10.1101/2022.10.10.510802
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

High-density linkage maps and chromosome level genome assemblies unveil direction and frequency of extensive structural rearrangements in wood white butterflies (Leptideaspp.)

Abstract: Karyotypes are generally conserved between closely related species and large chromosome rearrangements typically have negative fitness consequences in heterozygotes, potentially driving speciation. In the order Lepidoptera, most investigated species have the ancestral karyotype and gene synteny is often conserved across deep divergence, although examples of extensive genome reshuffling have recently been demonstrated. The genus Leptidea has an unusual level of chromosome variation and rearranged sex chromosome… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(17 citation statements)
references
References 99 publications
1
15
0
Order By: Relevance
“…As mentioned above, our results showed that the reduced recombination rate towards chromosome ends was not ubiquitous across all chromosomes; eight chromosome ends (one for each of the following chromosomes: 5, 6, 10, 11, 16, 25, 27 and 29) did not show a significant reduction in the recombination rate as compared to each respective intra-chromosomal level. Four of these exceptions (one chromosome end for each of chromosomes 5, 11, 25 and 27) coincide with recently identified fission and fusion polymorphisms segregating in the wood white population in Scandinavia (Höök et al 2022). These results show that fission/fusion events can have immediate effects on the distribution of crossover events within and between chromosomes.…”
Section: Genome-wide Distribution Of the Recombination Rate In Wood W...supporting
confidence: 83%
See 4 more Smart Citations
“…As mentioned above, our results showed that the reduced recombination rate towards chromosome ends was not ubiquitous across all chromosomes; eight chromosome ends (one for each of the following chromosomes: 5, 6, 10, 11, 16, 25, 27 and 29) did not show a significant reduction in the recombination rate as compared to each respective intra-chromosomal level. Four of these exceptions (one chromosome end for each of chromosomes 5, 11, 25 and 27) coincide with recently identified fission and fusion polymorphisms segregating in the wood white population in Scandinavia (Höök et al 2022). These results show that fission/fusion events can have immediate effects on the distribution of crossover events within and between chromosomes.…”
Section: Genome-wide Distribution Of the Recombination Rate In Wood W...supporting
confidence: 83%
“…A formal analysis showed that the recombination rate in the subtelomeres (last 5 100 kb windows at each end of the chromosomes) was significantly reduced (2.46 cM / Mb) compared to the 100 kb windows located in proximal positions of the chromosomes i.e., outside of the subtelomeric regions (Wilcoxon’s test, W = 1,310,856, p-value = 3.18 * 10 −66 ). It should be noted that this does not necessarily reflect a low recombination rate in the telomeres, but rather in the subtelomeric regions, since telomeric repeats were not covered in the wood white genome assembly (Höök et al 2022). We also analyzed each chromosome separately and found a reduction in recombination rate in subtelomeric regions in 50 out of the 58 chromosome ends (29 chromosome pairs, 2n = 58; Supplementary Table 1).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations